How School Principals Influence Student Learning - Elizabeth Dhuey; Justin Smith (Institute for the Study of Labor (IZA), 2014)
Many studies examine the importance of teachers in students' learning, but few exist on the contribution of principals. We measure the effect of principals on gains in primary test scores in North Carolina and estimate the standard deviation of principals' value added to be 0.12 -0.17. We find that the match between principals and schools accounts for a significant amount of principals' value added and also find that replacing the current principal has little effect on non-test score school inputs and outcomes regardless of the new principal's value added, but that brand new principals have a detrimental effect.
Keywords: I21; 330; economics of education; principals; school leadership